(untitled) (Iraqi Journal of Medical Sciences, 2009)
Background: Hepatitis A is an important endemic disease in Iraq. And Insulin dependent diabetes is one of serious chronic disease that affect children. Objective: To study the possible relationship between viral hepatitis A infection and occurrence of diabetes mellitus in Iraqi children. Method: A case control study was done on hundred newly diagnosed diabetic children, who were compared to hundred control children.Serological test were done to both groups to detect antibodies against Hepatitis A by using ELISA method .This study started on 1st of November 2006 and ended at 20th of December 2008 Both groups were collected from Al-Kadhymia Teaching Hospital and Al-Noor General Hospital. Result: There was slight increase incidence of diabetes mellitus in females (56%) than males (44%) and there was significant negative correlation between Hepatitis A and diabetes mellitus since 11% of diabetic children had positive serological test while 26% of control children had positive result. Conclusion:there was no relationship between hepatitis A infection and occurrence of IDDM. Keywords: Hepatitis A, diabetes mellitus, children.